MEASURING SERVICE QUALITY AND CUSTOMER SATISFACTION AT BANK SYARIAH SURABAYA WITH BIG DATA ANALYSIS - Laily Nisa, Fauzatul; Clara Dewanti, Mentari; Fitria Utami, Anisa; Nur Arumsari, Devinta (Universitas Islam Lamongan, 2024)
Banking institutions that provide sharia-based services in Indonesia still have a smaller number of customers compared to conventional banks, even though Indonesia is a country with the largest Muslim population in the world. Therefore, this study aims to observe customer satisfaction with Islamic banking services and help managers evaluate their performance. This research was conducted using big data analysis from reviews given by the public regarding 3 Islamic banks in Surabaya through the Google Maps website, including: Bank Syariah Indonesia Surabaya Jemur Handayani, Bank Syariah Surabaya Branch Office Dharmawangsa, and Bank Syariah Surabaya Branch Office Darmo. By using the textual review method, it is hoped that this research can provide an overview of social perspectives regarding service quality and customer satisfaction with Islamic banks and provide input for managers so that they can advance the Islamic economy, especially in Indonesia.